Transitioning to sustainable dietary patterns: learnings from animal-based and plant-based dietary patterns in French Canadian adults - Rochefort, Gabrielle; Brassard, Didier; Desroches, Sophie; Robitaille, Julie; Lemieux, Simone; Provencher, Véronique; Lamarche, Benoît (Frontiers in Nutrition, 2023)
Many dietary guidelines promote the substitution of animal proteins with plant-based proteins for health benefits but also to help transitioning towards more sustainable dietary patterns. The aim of this study was to examine the food and nutrient characteristics as well as the overall quality and costs of dietary patterns consistent with lower intakes of animal-based protein foods and with higher intakes of plant-based protein foods among French Canadian adults. Dietary intake data, evaluated with 24-hour recalls, from 1147 French-speaking adults of the PRÉDicteurs Individuels, Sociaux et Environnementaux (PREDISE) study conducted between 2015 and 2017 in Québec were used. Usual dietary intakes and diet costs were estimated with the National Cancer Institute’s multivariate method. Consumption of animal- and plant-based protein foods was classified into quarters (Q) and differences in food and nutrient intakes, Healthy Eating Food Index (HEFI)-2019 scores and diet costs across quarters were assessed using linear regression models adjusted for age and sex. Participants with lower intakes of animal-based protein foods (Q1 vs. Q4) had a higher HEFI-2019 total score (+4.0 pts, 95%CI, 0.9 to 7.1) and lower daily diet costs (-1.9 $CAD, 95%CI, -2.6 to -1.2). Participants with higher intakes of plant-based protein foods (Q4 vs. Q1) had a higher HEFI-2019 total score (+14.6 pts, 95%CI, 12.4 to 16.9) but no difference in daily diet costs (0.0$CAD, 95%CI, -0.7 to 0.7). In a perspective of diet sustainability, results from this study among French-speaking Canadian adults suggest that a shift towards a dietary pattern focused primarily on lower amounts of animal-based protein foods may be associated with a better diet quality at lower costs. On the other hand, transitioning to a dietary pattern focused primarily on higher amounts of plant-based protein foods may further improve the diet quality at no additional cost.